Airborne laser scanning data storage and indexing: state-of-the-art review. Issue 24 (16th December 2016) - Vo, Anh-Vu; Laefer, Debra F.; Bertolotto, Michela
ABSTRACT: While the rapid growth in the availability and quality of airborne laser scanning data offers unprecedented information, it challenges the existing data management and dissemination solutions. Data management has become a bottleneck to effective laser scanning data exploration. This paper documents the state-of-the-art techniques for aerial laser scanning (ALS) data storage and indexing during the post-processing stage. A brief history of laser scanning technology is presented with the intention to offer an overview about the evolution of the technology from the data point of view inclusive of full waveform data management. The key strategies for data handling, including data modelling and indexing, are extensively discussed.